Inflammation in Human Heart Failure: Major Mediators and Therapeutic Targets - Reina-Couto, Marta; Pereira-Terra, Patrícia; Quelhas-Santos, Janete; Silva-Pereira, Carolina; Albino-Teixeira, António; Sousa, Teresa (Frontiers in Physiology, 2021)
Inflammation has been recognized as a major pathophysiological contributor to the entire spectrum of human heart failure (HF), including HF with reduced ejection fraction, HF with preserved ejection fraction, acute HF and cardiogenic shock. Nevertheless, the results of several trials attempting anti-inflammatory strategies in HF patients have not been consistent or motivating and the clinical implementation of anti-inflammatory treatments for HF still requires larger and longer trials, as well as novel and/or more specific drugs. The present work reviews the different inflammatory mechanisms contributing to each type of HF, the major inflammatory mediators involved, namely tumour necrosis factor alpha, the interleukins 1, 6, 8, 10, 18 and 33, C-reactive protein and the enzymes myeloperoxidase and inducible nitric oxide synthase, and their effects on heart function. Furthermore, several trials targeting these mediators or involving other anti-inflammatory treatments in human HF are also described and analysed. Future therapeutic advances will likely involve tailored anti-inflammatory treatments according to the patient’s inflammatory profile, as well as the development of resolution pharmacology aimed at stimulating resolution of inflammation pathways in HF.